The efficiency of structural support and impact on economic and social indicators - Dumciuviene, Daiva; Stundziene, Alina (Technological and Economic Development of Economy, 2015)
The economic and social cohesion is one of the economic objectives of the European Union. It is, therefore, important to analyse the impact of policies of the European Union on cohesion. The establishment of the common market still did not offer a solution for economic problems faced by the Member States. The economic and social cohesion is very important to strengthen the political and economic development of the Member States. This article includes the analysis of Lithuanian economic environment compared with the other Member States and the impact of EU structural funds on economic growth of the country. The detailed analysis of the correlation between funding and economic and social indicators of Lithuania showed that there is the significant direct relationship between the funding and the direct foreign investments per inhabitant. The significant correlation between EU support and other economic and social indicators was not found. Nevertheless the EU funding is undoubtedly useful and necessary to promote the economic growth. The efficiency of the use of EU funds is the largest problem and the task achieving the maximum benefit for the economics of Lithuania.